Salford Twist Mill: Uncovering an Iconic Textile Factory. - Miller, Ian (Industrial Archaeology Review, 2024)
The Salford Twist Mill of 1799–1801 has attracted much attention as a pioneering example of an iron-framed building, the first textile mill in England to have benefited from steam heating and one of the earliest buildings in the world to have been permanently lit by gas. Aspects of the mill's development have been debated since its destruction in the mid-20th century, although several points of contention were clarified during an archaeological excavation and associated research conducted by the University of Salford in 2016–17. In particular, fragments of structural ironwork recovered from demolition layers yielded fresh evidence for the building's internal cast-iron frame, and excavation of the engine room enabled details of the power-transmission system to be elucidated. Whilst this article necessarily recites earlier work, it combines the key findings from the recent investigation with a review of previous studies to provide a definitive account of one of the first iron-framed mills.